2016
DOI: 10.1097/dss.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Photonumeric Scale for Evaluation of Transverse Neck Lines

Abstract: BACKGROUNDA validated scale is needed for objective and reproducible comparisons of horizontal neck lines before and after treatment in practice and clinical studies.OBJECTIVETo describe the development and validation of the 5-point photonumeric Allergan Transverse Neck Lines Scale.METHODSThe Allergan Transverse Neck Lines Scale was developed to include an assessment guide, verbal descriptors, morphed images, and real subject images for each scale grade. The clinical significance of a 1-point score difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
1
32
0
3
Order By: Relevance
“…Recent research has shown slightly greater esthetic improvements when patients are treated in this manner in the neck area . Results were very consistent between the independent evaluators and observed with three different validated grading scales (one for necklines and two for the décolletage), illustrating the robustness of the treatment results. The Merz Aesthetics scale offers a further advantage relative to other scales by providing a dynamic assessment (ie while contracting the breast area by pulling the arms together toward the medial line) in addition to a static assessment.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Recent research has shown slightly greater esthetic improvements when patients are treated in this manner in the neck area . Results were very consistent between the independent evaluators and observed with three different validated grading scales (one for necklines and two for the décolletage), illustrating the robustness of the treatment results. The Merz Aesthetics scale offers a further advantage relative to other scales by providing a dynamic assessment (ie while contracting the breast area by pulling the arms together toward the medial line) in addition to a static assessment.…”
Section: Discussionsupporting
confidence: 72%
“…At the first visit and before the treatment, subjects underwent a pretreatment evaluation by the investigator. Three scales were used to assess skin laxity and wrinkling in the neck and décolletage area at baseline: the Merz Aesthetics Décolleté wrinkles at rest scale, the Fabi‐Bolton chest wrinkle scale, and the Allergan transverse neck lines scale . The Merz and Fabi‐Bolton scales are both validated five‐point scales for the décolletage area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 But horizontal neck wrinkles are not entirely caused by aging, as they are often observed in children and young adults. 7,8 Importantly, age-related skin laxity can worsen these wrinkles. 1,2,7 Frequent bending of the neck to look at cell phones, tablets, or books could also cause wrinkle development in the young.…”
Section: Introductionmentioning
confidence: 99%